Pulsed laser remelting of A384 aluminum, part II: Modeling of surface homogenization and topographical effects. (April 2018) - Richter, Brodan; Chen, Shixuan; Morrow, Justin D.; Sridharan, Kumar; Eriten, Melih; Pfefferkorn, Frank E.
Abstract: A simulation model is developed for pulsed laser remelting that captures the homogenization of surface chemical composition and height variations that occur due to silicon (Si) precipitates in a hypereutectic aluminum-silicon (Al-Si) casting alloy. The model simulates remelting pulse-by-pulse with two sequential and repeated steps: it first predicts surface homogenization by areal averaging within a laser spot and then generates and adds a surface feature, due to thermocapillary flow, whose size depends on the concentration of Si within the homogenized spot. Compositional data of remelted lines was collected with energy-dispersive x-ray spectroscopy and used to verify the homogenization step of the simulation model. It was found that Si precipitates get redistributed by the laser with the peak in Si concentration occurring in the direction opposite that of beam travel. Height data from remelted lines were measured using white light interferometry to verify the accuracy of the remelting model in simulating surface topographical modifications. It was found that variations of approximately ± 1 μm are induced in the Al-Si alloy during pulsed laser remelting due to the Si proeutectic precipitates. This is attributed to differences in laser absorption of Si and Al. Because the Si precipitates absorb more energy from the laser, they experience higher temperatures and temperature gradients, which cause larger thermocapillary flow. The results provide insights into approaches to model surface compositional homogenization that occurs during laser remelting and provides an understanding of surface microstructural and topographical features often seen in laser polished Al-Si casting alloys.